2021
DOI: 10.1109/access.2021.3053956
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced YOLO v3 Tiny Network for Real-Time Ship Detection From Visual Image

Abstract: Different from ship detection from synthetic aperture radar (SDSAR) and ship detection from spaceborne optical images (SDSOI), ship detection from visual image (SDVI) has better detection accuracy and real-time performance, which can be widely used in port management, cross-border ship detection, autonomous ship, safe navigation, and other real-time applications. In this paper, we proposed a new SDVI algorithm, named enhanced YOLO v3 tiny network for real-time ship detection. The algorithm can be used in video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 39 publications
0
52
0
Order By: Relevance
“…The clustering results are sorted by area size as (23,29), (37,34), (26,53), (41, 53), (41, 90), (94, 40), (61, 75) and (78, 135). It can be found that the scales of the prior boxes are quite different, and they are assigned to 76 × 76, 38 × 38, 19 × 19 three feature maps as the prior boxes.…”
Section: Model Training Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The clustering results are sorted by area size as (23,29), (37,34), (26,53), (41, 53), (41, 90), (94, 40), (61, 75) and (78, 135). It can be found that the scales of the prior boxes are quite different, and they are assigned to 76 × 76, 38 × 38, 19 × 19 three feature maps as the prior boxes.…”
Section: Model Training Results and Analysismentioning
confidence: 99%
“…Teng et al [ 25 ] used a well-known feature extractor model and the YOLOv2 network to detect a concrete crack. Li et al [ 26 ] proposed an enhanced YOLOv3 tiny network for real-time ship detection. Yolo is also widely used in radar images and remote sensing images.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the maximum pooling and mean pooling are performed on the input images, respectively, under the spatial attention module. Then a convolution layer is used to learn the new feature map [26]. where the Max represents the maximum pool processing, the Avg represents the global average pooling processing, the Conv represents the convolution layer,  represents the sigmoid activation function.…”
Section: Introduction Of Attention Mechanismmentioning
confidence: 99%
“…Firstly, the maximum pooling and mean pooling are performed on the input images, respectively, under the spatial attention module. Then a convolution layer is used to learn the new feature map [26].…”
Section: Introduction Of Attention Mechanismmentioning
confidence: 99%
“…A region suggestion generator is formed, where features are extracted, and a classifier is used to predict the category of the proposed area. The latter includes YOLO [29], SSD [30], etc., which directly makes classification and prediction for the objects in each position of the feature map. The intelligent algorithm of target detection based on CNN has realized improvement of the detection speed and accuracy, and has great advantages compared with traditional target detection algorithms.…”
Section: Introductionmentioning
confidence: 99%